Strategı Penerapan Pembelajaran Flash Card dalam Mengatası Kesulıtan Membaca pada Anak Usıa Dını dı TK Bhaktı 5 Kp. Sumur Peteuy Baros Kabupaten Serang - Dewi, Lina Marliana; Meliyawati, Meliyawati; Gentari, Ratu Erlina (Jurnal Artikula, 2022)
This study aims to examine the strategy of implementing flash card learning in overcoming reading difficulties in early childhood at TK Bhakti 5 Kp. Peuteuy Baros Well. One of the abilities that must be developed in early childhood is the ability to learn to read Indonesian. The research method used was action research with the form of research used descriptive. The instruments used in this study were observations, interviews, field notes and documentation. The subjects in this action research are parents and children aged 5 years, with a total of 20 children. This action research was conducted in 3 cycles and in each cycle two meetings. Each cycle consists of four stages of activity, namely, planning, action, observation, and reflection. To obtain data sources and about the children's ability to read, the researchers collaborated with teachers and parents. Based on the results of the implementation of actions on reflection I and reflection II and reflection III, it can be stated that there is an increase in quality in overcoming reading difficulties (both activity and results) with the strategy of implementing flash cards. The implementation of this research has reached 100% of the entire activity procedure.